UPAYA GURU MENGENAL KARAKTERISTIK SISWA MELAUI SUPERVISI KELAS DI SDN 002 NONGSA TAHUN PELAJARAN 2018/2019 - Supriati, Supriati (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
Efforts to recognize character education programs (PPK), there are five main values ​​in the character of PPK, namely religious, nationalist, independent, mutual cooperation, and integrity. Education is a very important element in the development of the Indonesian nation. Especially school is the basic foundation in forming the mental and character of the nation's generation. Through PPK in the classroom by integrating the core character values ​​in the learning process. The teacher is one of the character forms of students in school. The purpose of this research is to instill the values ​​forming the character of students to effectively prioritize certain values, so that the education of students has characters that can change behavior, ways of thinking, and ways of acting. The research subject was a class teacher at SDN 002 Nongsa in the 2018/2019 academic year. Researchers used school action research (School Action Research). Data collection techniques using observation and instrument sheets. Based on the results of the study, it can be concluded that in class supervision in recognizing the character of students. cycle II 90%, but there are still teachers who are below average in conducting classroom supervision.